Ultrastructure and innervation of regenerated intrafusal muscle fibres in heterochronous isografts of the fast rat muscle - Soukup, T; Novotová, M (Acta neuropathologica, 2000)
Extensor digitorum longus (EDL) muscles from 2- to 28-day-old rats were grafted into EDL muscles of adult inbred recipients (n = 8). At 1-6 months after the operation, experimental muscles were excised and the ultrastructure and innervation of regenerated muscle spindles was examined. Regenerated muscle spindles (n = 36) in isografted EDL muscles contained 4.3 +/- 0.2 (mean +/- SEM) encapsulated muscle fibres. These "intrafusal" muscle fibres lacked nuclear bag and nuclear chain accumulations, which are characteristic of normal muscle spindles; thus, they rather resembled thin encapsulated extrafusal muscle fibres. In the same sample, myelinated axons were found in 33 (92%) muscle spindles, but no sensory terminals were found. These findings demonstrate that regenerated spindles in isografted EDL muscles were not reinnervated by spindle-specific sensory axons, but exclusively by motor axons. Typical intracapsular motor endplates (MEPs) were found in one third of regenerated spindles examined. Their motor terminals contained accumulated mitochondria and synaptic vesicles. As is characteristic for MEPs, axolemma and sarcolemma were separated by a synaptic cleft about 60 nm wide that contained a basal lamina. The underlying sarcolemma formed either small infoldings or none at all, and the subsynaptic area contained only small subsarcolemmal accumulations of mitochondria. It is apparent that the structures described here as "regenerated muscle spindles" do not perform their normal physiological function as stretch receptors because they lack the sensory innervation. The present results show that regeneration and reinnervation in heterochronous isografts corresponds to that previously described in autotransplanted free muscle grafts. The results also show that, during muscle spindle regeneration, intrafusal satellite cells develop into extrafusal-like muscle fibres, apparently due to their motor innervation.
Keywords: Myelin Sheath; Rats, Inbred Lew; axony; Motor Neurons; Female; krysa rodu Rattus; Neurons, Afferent; svalová vlákna typu II; zvířata; Nerve Regeneration; regenerace nervu; Transplantation, Homologous; Muscle Fibers, Fast-Twitch; kosterní svaly; ženské pohlaví; Muscle, Skeletal; Muscle Spindles; regenerace; nervosvalová vřeténka; potkani inbrední LEW; Rats; Axons; motorické neurony; neurony aferentní; Animals; homologní transplantace; myelinová pochva; Regeneration